Models of Invisibility: Rendering Domestic and Other Gendered Violence Visible to Students Through Clinical Law Teaching. (October 2016) - MacDowell, Elizabeth L.; Cammett, Ann
The proliferation of university courses about domestic violence includes clinical courses in law schools in which students represent victims in their legal cases. This essay advocates for a broader approach to teaching about the problem. Using examples from their clinic cases, the authors show how teachers can overcome pedagogical challenges and render domestic and other forms of gendered violence, including state and community violence, more visible to students by intentionally raising and placing it within larger frameworks of structural inequality. In this way, students learn to identify and address gendered violence even when it is not the presenting problem.